Tuning solid state emission of semisquaraines via trimming central-ring structures. (February 2020) - Liang, Kangli; Shao, Qingqing; Xia, Guomin; Wang, Yigang; Jiang, Lixia; Hong, Liming; Wang, Hongming
Abstract: Adjusting the emission wavelength and intensity of organic luminogens by precisely manipulating structures has always been a major challenge. In this study, three ABT-based semisquaraines SQ1-3 have been designed and synthesized by trimming the central four-membered ring with ethyoxyl or chloric group. From spectral analysis, all of them exhibited weak emission in dilute solution, but red, yellow to green emission color was verified in their crystal state with ΦPL from 0.13, 0.35 to 0.58, respectively. From structural analysis, the increase of electron-deficient chloric groups in SQ3 not only led to more facile ESIPT process and distorted configuration, but also resulted in a rare H-aggregated formation with extremely weak π-π interactions in crystalline state, which synergistically facilitated its highest ΦPL of 0.58 at shortest emission wavelength of 538 nm. Additionally, typical ESIPT and AIE property was examined and furtherly proved by the TDDFT calculations in all these molecules. Graphical abstract: Image 1 Highlights: Trimming the semisquarines SQ1-3 resulted into tunable solid-state emision from green to red. Different electron distribution and packing modes responded to the distinct emissions in SQ1-3 crystals. ESIPT process and AIE behaviors of SQ1-3 were verified by experimental and DFT results.